Sustained Vaccination Coverage during the Coronavirus Disease 2019 Epidemic in the Republic of Korea - Jeong Hee Yu; Hang jin Jeong; Seon Ju Kim; Jae Young Lee; Young June Choe; Eun Hwa Choi; En Hi Cho (Vaccines, 2020)
Amid the COVID-19 pandemic, vaccination coverage may decline due to limited accessibility to healthcare. We assessed the impact of the COVID-19 pandemic on vaccination coverage and the incidence of vaccine-preventable diseases (VPDs) in the Republic of Korea. National vaccination coverage of 10 essential vaccines administered to children between January–June 2019 and January–June 2020 was analyzed. The national incidence of selected VPDs was compared for the corresponding periods. During the COVID-19 outbreak, the vaccination rate in children aged 0–35 months in Korea did not decrease significantly, whereas the vaccination rate for children aged 4–6 years decreased by 1.4–1.9%. The overall incidence of VPDs decreased by 10–50% between 2019 and 2020, especially with varicella. Thus, the COVID-19 pandemic did not result in a decrease in vaccination coverage among Korean children, which prevented a surge in VPD incidence. Maintaining essential vaccination coverage without interruption is important during the response to the COVID-19 pandemic.